Channel estimation relying on the minimum bit‐error‐ratio criterion for BPSK and QPSK signals. Issue 1 (1st January 2014) - Dutta, Amit Kumar; Hari, K.V.S.; Hanzo, Lajos
Abstract : The authors consider the channel estimation problem in the context of a linear equaliser designed for a frequency selective channel, which relies on the minimum bit‐error‐ratio (MBER) optimisation framework. Previous literature has shown that the MBER‐based signal detection may outperform its minimum‐mean‐square‐error (MMSE) counterpart in the bit‐error‐ratio performance sense. In this study, they develop a framework for channel estimation by first discretising the parameter space and then posing it as a detection problem. Explicitly, the MBER cost function (CF) is derived and its performance studied, when transmitting binary phase shift keying (BPSK) and quadrature phase shift keying (QPSK) signals. It is demonstrated that the MBER based CF aided scheme is capable of outperforming existing MMSE, least square‐based solutions.